Quercetin inhibits acid-sensing ion channels through a putative binding site in the central vestibular region. (21st April 2017) - Mukhopadhyay, Mohona; Singh, Anurag; Sachchidanand, S.; Bera, Amal Kanti
Highlights: Quercetin inhibits ASICs with an IC50 of ∼2 µM. In HEK-293 cells quercetin inhibits low pH-induced calcium entry and cell death. Quercetin effect is specific to ASICs as it doesn't inhibit several other channels. We identified four residues which seem to interact with Quercetin. It could be a potential therapeutic candidate for targeting ASICs. Abstract: Acid-sensing ion channels (ASICs) are associated with many pathophysiological processes, such as neuronal death during ischemic stroke, epileptic seizure and nociception. However, there is a dearth of ASIC-specific therapeutic blockers. Here we report that quercetin, a plant flavonoid, which is known for its neuroprotective effect, reversibly inhibits homomeric rat ASIC1a, ASIC2a and ASIC3 with an IC50 of about 2 µM. Also, quercetin prevents low pH-induced intracellular calcium rise and cell death in HEK-293 cells, which have endogenous expression of ASIC1a and 2a. The inhibitory effect of quercetin on ASICs is not due to membrane perturbation, as it did not have any effect on other channels, like NMDA receptor, GABAA receptor and P2X4 receptor. Unlike quercetin, another flavonoid resveratrol had no effect on ASIC1a. Computational analysis revealed that quercetin binds to the channel in a cavity at the central vestibule, lined by several charged residues like Q276, R369, E373 and E416 in ASIC1a. Mutation of Arg369 to Ala or Glu416 to Gln abolished the inhibitory effect of quercetin on rat ASIC1a completely, while Glu373 to Gln showed reduced sensitivity. Our results raise the possibility of using quercetin for targeting ASICs in vivo .